A rare late complication of laparoscopic cholecystectomy - Little, Mhairi (BMJ Publishing Group, 2013)
An 86-year-old woman presented three years after laparoscopic cholecystectomy with right upper quadrant pain and raised inflammatory markers. Liver function tests were normal; however, a previous ultrasound scan suggested a common bile duct stone so she was treated for cholangitis secondary to choledocholithiasis. Repeat ultrasound scan again showed a common bile duct (CBD) stone and also a subdiaphragmatic abscess. CT scan confirmed the abscess, associated with a surgical clip from her previous surgery. There was no evidence of a persistent CBD stone on the CT scan. She was treated conservatively with intravenous antibiotics and her symptoms improved. Follow-up MRI did not show any choledocholithiasis. Surgical clips causing delayed abscess formation are very unusual. We discuss the presentation, investigations and treatment of this interesting case. Existing relevant literature is reviewed, and management strategies to treat such rare complications are suggested.